Manfaat dan Peningkatan Soft Skills Melalui Program Magang Non-Mbkm di Koperasi Syari’ah Serba Usaha Salimah (Kossuma) - Ridhwan Ridhwan; Natasha Aurora Geraldine; Reiza Nur Shafitri; Nazla Hanifa; Putri Ajeng Pembayung (Peneliti.net, 2023)
This research is to find out the benefits and impacts of the non-MBKM internship program for students of the Faculty of Economics and Business (FEB) Jambi University (UNJA), namely in improving soft skills and knowing the benefits of apprenticeships. This research was conducted at the Salimah Multi-Business Cooperative Syari'ah (KOSSUMA). The result is that FEB students participating in this non-MBKM internship program are getting soft skills about bookkeeping, filing and about financial management. When they finish participating in this non-MBKM internship program, students will be ready if they enter the world of work the next day. This program also has benefits for students, benefits for cooperatives and benefits for FEB UNJA.